Taming the complexity of large models. (6th September 2013) - Oberhardt, Matthew; Ruppin, Eytan
Abstract : There are many complex biological models that fit the data perfectly and yet do not reflect the cellular reality. The process of validating a large model should therefore be viewed as an ongoing mission that refines underlying assumptions by improving low‐confidence areas or gaps in the model‧s construction.